Peran Kepemimpinan dalam Meningkatkan Budaya Keselamatan Pasien di Rumah Sakit (Suatu Kajian Kepustakaan) - Nikita Nabilla; Dhamanti, Inge (Jurnal Kesehatan Komunitas, 2023)
One of the elements that contribute to patient safety issues is poor leadership. Leadership is an essential component of changing the culture of patient safety. This literature review aims to examine the role of leadership in enhancing hospital patient safety culture. The method employed is a review of the literature using articles published between 2017 and 2022. The literature was gathered using the terms "leadership," "patient safety culture," and "hospital" from two database sources: Garuda Portal and Google Scholar. According to the keywords, the search yielded 77 articles. Five articles were evaluated after being screened using inclusion criteria. According to the five articles obtained, there are five leadership roles in improving patient safety culture: encouraging and ensuring the implementation of the Seven Steps Toward Hospital Patient Safety, ensuring ongoing programs to identify patient safety risks and reduce incidents, encouraging and fostering communication and coordination between units and individuals, allocating adequate resources, and measuring and reviewing the effectiveness. It is expected that hospital leaders can show commitment to making the hospital institution safe by implementing five leadership roles and involving staff in the commitment.